Technology crossing borders : (Harvard Business School Press, 1984)
The empirical work in this book examines three issues in the transfer of technology. How managers, public and private, choose the kinds of technology they import or export. How multinational enterprises decide on the channels through which they transfer. technology and how that choice affects the recipient firm abroad; and how multinational enterprises manage certain of their relationships with overseas affiliates that import, use, modify, and generate technology. This book makes no attempt to summarize all the literature in the fields on which it reports; rather, it presents a group of clearly related empirical studies that draw on a common set of concepts. On some points the studies are in agreement with the conventional literature; on others, they depart strikingly from the more commonly accepted theories.